Technological applications - Scruggs, Thomas E., 1948-; Mastropieri, Margo A., 1951- (Advances in learning and behavioral disabilities, 2001)
Recent years have witnessed an explosion of technological advances, which has transformed virtually every aspect of human existence. Prominent among these advances are assistive technologies, which have been employed to improve the quality of life for individuals with disabilities. In this volume, recent advances in technological applications for individuals with learning and behavioural disabilities are described and discussed, in a collection that includes reviews of research, and original research reports. Technologies in this area have provided a multiplicity of uses, from advances in tools for basic research to text and content-enhancements to promote learning and behaviour change in educational environments. Discussed in this volume are technologies for improving our understanding of eye movements in learning from text, as well as technological applications in reading and literacy development. These technologies are employed to promote learning within classrooms, and also to connect learners with mentors outside the classroom. Beyond text, the use of virtual reality has been employed to promote understanding of complex concepts in physics. In many cases, these technologies have been employed effectively with students with emotional or behavioural disorders. Also discussed are issues in technological applications, including considerations of the most effective and appropriate uses of technology, where research is or should be heading, and teachers' understandings of the uses of technology with students with learning and behavioral disabilities. Also included in this volume are discussions of issues in learning disabilities, including discussions of significant issues in discrepancy models, and strategic coherence of individuals with learning difficulties. Overall, the ten chapters in this volume aim to provide some of the most current thinking and applications in learning and behavioural disabilities.